EFEKTIVITAS PROGRAM REDISTRIBUSI GURU PNS PADA SMK NEGERI DI KOTA ADMINISTRATIF JAKARTA SELATAN - Djoko Susilo; Akhmad Shunhaji; Otong Surasman (el-Moona: Jurnal Ilmu Pendidikan Islam, 2020)
Djoko Susilo: The effectiveless of PNS Teachers Redistribution Program in State Vocational Schools in the Administrative City of South Jakarta. The civil servant teacher redistribution program began to be implemented in DKI Jakarta in 2015, by rotating senior teachers. At the beginning of the redistribution program, there was a shock at the State Vocational High School in South Jakarta. A wave of objections to following up on this program was widely voiced by old teachers, who incidentaly were the objeck of the implementers in the field. However, because the rules have been made, when the redistribution decree is issued, teachers whose names appear will still have to move, teaching in the new school. This study aims to analyze the effectiveness of the teachers redistribution program for civil servants in the vocational High School in the South Jakarta Administrative City area and find alternative solution in maintaining the stability of the teachers’ motivation. The redistribution program is already underway and implemented in the field. Although all the respondent teachers were asked what was the first reaction that came after the redistribution decree was isssued, all said they were shocked and suprised. However, after carrying out the task, most of the redistribution teachers have been able to adapt in the new education unit. But there are also teachers respondent who, although they have been rotated for a long time, have a desire to return to old school. In general, the redistribution program of PNS teachers at State Vocational Schools in the South Jakarta Administration city ran effectively.